Heavy oil catalytic cracking method, heavy oil catalytic cracking catalyst and preparation method thereof
Patent Information
- Application Number
- CN202611263032.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]为解决上述现有技术中存在的问题,本发明的目的在于提供一种重油催化裂解方法、重油催化裂解催化剂及其制备方法,以解决现有技术中乙烯产率低的问题
[0033] This application modifies a silicon source by applying alkaline earth metals, boron, and rare earth elements to obtain a modified silicon material. It also modifies a ZSM-5 molecular sieve using metal nanoparticles to obtain a modified ZSM-5 molecular sieve. A catalyst is obtained by mixing a Y-type molecular sieve with the modified silicon material, the modified ZSM-5 molecular sieve, clay, and binder, followed by slurry preparation, spray drying, and calcination. This process creates a gradient pore design with different pore sizes, which is beneficial for the hierarchical and tandem cracking reaction of heavy oil macromolecules. In this application, the modified silicon material forms the first active center, promoting both the pre-cracking reaction of heavy oil macromolecules and the alkane radical cracking reaction to generate ethylene, thus increasing ethylene production. The Y-type molecular sieve serves as the second active center, further catalyzing the pre-cracking macromolecules with acid. The modified ZSM-5 molecular sieve acts as the third active center, promoting the cracking of carbocations to generate ethylene and propylene. This three-active-center design achieves efficient cracking of heavy oil macromolecules while enabling precise selection of low-carbon olefins, effectively increasing the yield of ethylene, propylene, and butene, especially ethylene.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and in particular to a method for catalytic cracking of heavy oil, a catalyst for catalytic cracking of heavy oil, and a method for preparing the same. Background Technology
[0002] Ethylene, propylene, and butene are important basic organic chemicals widely used in chemical, pharmaceutical, and materials industries. Their primary industrial production method is the steam cracking of light hydrocarbons. Steam cracking requires light hydrocarbon feedstocks such as ethane, propane, and naphtha, and must be carried out at temperatures above 800°C. This results in insufficient feedstock availability and enormous energy consumption. Catalytic cracking of heavy oil to produce low-carbon olefins can effectively overcome these drawbacks. Catalytic cracking operates at temperatures 100-300°C lower than steam cracking, significantly reducing energy consumption. One of the key technologies for catalytic cracking is catalyst preparation technology.
[0003] Existing heavy oil catalytic cracking technologies generally employ catalyst systems that combine Y-type molecular sieves with other molecular sieves (such as ZSM-5, β-zeolite, etc.). For example, CN101310858A discloses a heavy oil catalytic cracking catalyst, which is mainly composed of USY-type molecular sieves, with the addition of β-zeolite-mordenite eutectic molecular sieve additives. Based on the weight percentage of the catalyst, the content of USY-type molecular sieve is 10-50%, the content of β-zeolite-mordenite eutectic molecular sieve is 10-20%, the binder is 5-50%, and the clay is 10-75%. It is a molecular sieve with β-zeolite and mordenite structural units; for example, CN115532305B discloses a catalyst for the catalytic cracking of heavy oil to produce gasoline and low-carbon olefins, its preparation method and application, the catalyst contains 30-79% by weight of support, 5-15% by weight of phosphorus-containing and metal core-shell molecular sieve, 15-45% by weight of Y-type molecular sieve, and 1-10% by weight of molecular sieve with a pore opening diameter of 0.65-0.70 nm; wherein, the core phase of the phosphorus-containing and metal core-shell molecular sieve is ZSM-5 molecular sieve, and the shell is β molecular sieve.
[0004] The aforementioned approaches generally suffer from unsatisfactory yields of low-carbon olefins (ethylene, propylene, and butene). While existing catalyst formulations, with their acidic centers and pore structures, are beneficial for the initial cracking of heavy oil macromolecules, they lack selectivity for the secondary cracking reactions that generate low-carbon olefins. This results in a higher proportion of middle fractions such as gasoline and diesel in the reaction products, while the yields of the target products, ethylene, propylene, and butene, are lower. Furthermore, during the catalytic cracking of heavy oil, side reactions such as hydrogen transfer, aromatization, and condensation compete with the olefin-generating reactions. The acidic centers in the aforementioned approaches may more readily promote these side reactions, leading to further consumption of the generated low-carbon olefins, converting them into dry gas (such as methane and ethane), coke, or aromatics, thereby reducing the overall yield of low-carbon olefins.
[0005] Therefore, how to provide a heavy oil catalytic cracking catalyst and its preparation method to improve the yield of ethylene, propylene, and butene, especially the yield of ethylene, has become an urgent problem to be solved. Summary of the Invention
[0006] To address the problems existing in the prior art, the present invention aims to provide a heavy oil catalytic cracking method, a heavy oil catalytic cracking catalyst, and a method for preparing the same, so as to solve the problem of low ethylene yield in the prior art.
[0007] To achieve the above-mentioned objective, this invention provides a method for preparing a heavy oil catalytic cracking catalyst, comprising the following steps:
[0008] 1) Prepare an alkaline earth metal solution and a boron-containing solution, add the alkaline earth metal solution and the boron-containing solution to a silicon source solution, mix them evenly, then add a rare earth compound, and after aging, obtain a modified silicon material;
[0009] 2) Prepare a modified metal nanoparticle solution, impregnate the modified metal nanoparticle solution with ZSM-5 molecular sieve, and then filter, dry and calcine to obtain modified ZSM-5 molecular sieve;
[0010] 3) The modified silicon material, the modified ZSM-5 molecular sieve, the Y-type molecular sieve, clay and binder and deionized water are mixed and pulped, then sprayed to form microspheres, and then calcined to obtain a heavy oil catalytic cracking catalyst.
[0011] According to one technical solution of the present invention, the alkaline earth metal in the alkaline earth metal solution is at least one of Be, Mg, Ca, and Sr; the mass content of the alkaline earth metal in the alkaline earth metal solution, calculated as oxides, is 0.5-20%.
[0012] The boron-containing solution is any one of boric acid, trimethyl borate, and triethyl borate, and the boron-containing solution is soluble in water or hydrolyzable.
[0013] The silicon source in the silicon source solution is one or more of the following: tetraethyl orthosilicate, water glass, coarse-porous silica gel, silica sol, fumed silica, or activated clay.
[0014] The rare earth compound is one or more of rare earth nitrate, rare earth chloride, and rare earth carbonate.
[0015] According to one technical solution of the present invention, the alkaline earth metal solution is prepared using an alkaline earth metal salt, wherein the alkaline earth metal salt is at least one selected from carbonates, nitrates, nitrites, sulfates, thiocyanates, phosphates, hydrogen phosphates, and chlorides.
[0016] The solvent for the alkaline earth metal solution is water or a mixture of water and alcohol containing at least one of methanol, ethanol, propanol, ethylene glycol, propylene glycol, or glycerol.
[0017] According to one technical solution of the present invention, the preparation of the modified metal nanoparticle solution specifically includes:
[0018] A nanoparticle solution was prepared using a precursor salt of modified metal nanoparticles; a nanoparticle dispersant was added to the nanoparticle solution, followed by a liquid-phase chemical reducing agent to carry out a liquid-phase reduction reaction, thereby obtaining modified metal nanoparticles.
[0019] The modified metal nanoparticles are at least one of Fe, Co, Ni, Cu, and Ag, and the average particle size of the modified metal nanoparticles is 0.5~200 nm.
[0020] The nanoparticle dispersant is at least one of ethylene glycol, propylene glycol, glycerin, polyacrylamide, and polyvinylpyrrolidone.
[0021] The nanoparticles are at least one of the following: modified metal, metal oxide, and metal sulfide.
[0022] The precursor salt of the modified metal nanoparticles is at least one of the nitrate, acetate, and chloride salts of the modified metal;
[0023] The nanoparticle solution contains 0.5-30% modified metal elements.
[0024] According to one technical solution of the present invention, the silicon-aluminum ratio of the ZSM-5 molecular sieve is 10~300;
[0025] The Y-type molecular sieve is at least one of rare earth Y-type molecular sieve, rare earth hydrogen Y-type molecular sieve, ultrastable Y-type molecular sieve and high silica Y-type molecular sieve.
[0026] According to one technical solution of the present invention, the clay is at least one selected from soapstone, bentonite, kaolin, montmorillonite, diatomaceous earth, rettoitite, sepiolite, halloysite, attapulgite, hydrotalcite, and quasi-haloysite.
[0027] The binder is one or more of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, zirconium oxide, thorium oxide, and beryllium oxide.
[0028] According to one aspect of the present invention, a heavy oil catalytic cracking catalyst is provided, which is prepared by the above-described method for preparing a heavy oil catalytic cracking catalyst, wherein the heavy oil catalytic cracking catalyst comprises the following components in weight percentage: 20-50% ZSM-5 molecular sieve, 5-15% Y-type molecular sieve, 0.5-5% boron-containing compound, 0.5-5% modified metal nanoparticles, 0.5-5% rare earth oxides, and the remainder being clay and binder.
[0029] According to one aspect of the present invention, a method for catalytic cracking of heavy oil is provided, wherein heavy oil is contacted with a catalyst under catalytic cracking conditions and a catalytic cracking reaction is carried out under the action of high-temperature steam; wherein the catalyst is the above-mentioned heavy oil catalytic cracking catalyst.
[0030] According to one technical solution of the present invention, the heavy oil is one or more of vacuum residue, atmospheric residue, vacuum gas oil, atmospheric gas oil, coking wax oil, deasphalted oil, and hydrotreated oil.
[0031] According to one technical solution of the present invention, the reaction conditions of the catalytic cracking reaction are: reaction temperature of 510~700℃, reaction time of 0.1~20s, catalyst-to-oil mass ratio of 6-40:1, and steam-to-heavy oil mass ratio of 0.1~1:1.
[0032] Compared with the prior art, the heavy oil catalytic cracking catalyst and its preparation method provided by the present invention have the following significant technical effects:
[0033] This application modifies a silicon source by applying alkaline earth metals, boron, and rare earth elements to obtain a modified silicon material. It also modifies a ZSM-5 molecular sieve using metal nanoparticles to obtain a modified ZSM-5 molecular sieve. A catalyst is obtained by mixing a Y-type molecular sieve with the modified silicon material, the modified ZSM-5 molecular sieve, clay, and binder, followed by slurry preparation, spray drying, and calcination. This process creates a gradient pore design with different pore sizes, which is beneficial for the hierarchical and tandem cracking reaction of heavy oil macromolecules. In this application, the modified silicon material forms the first active center, promoting both the pre-cracking reaction of heavy oil macromolecules and the alkane radical cracking reaction to generate ethylene, thus increasing ethylene production. The Y-type molecular sieve serves as the second active center, further catalyzing the pre-cracking macromolecules with acid. The modified ZSM-5 molecular sieve acts as the third active center, promoting the cracking of carbocations to generate ethylene and propylene. This three-active-center design achieves efficient cracking of heavy oil macromolecules while enabling precise selection of low-carbon olefins, effectively increasing the yield of ethylene, propylene, and butene, especially ethylene. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of this application can be combined with each other. The following embodiments only illustrate several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the patent application. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of this application, and these all fall within the protection scope of this application.
[0036] This invention provides a method for preparing a heavy oil catalytic cracking catalyst, comprising the following steps:
[0037] 1) Prepare an alkaline earth metal solution and a boron-containing solution, add the alkaline earth metal solution and the boron-containing solution to the silicon source solution, mix them evenly, then add rare earth compounds, and obtain modified silicon materials after aging;
[0038] 2) Prepare a modified metal nanoparticle solution. Impregnate the modified metal nanoparticle solution with ZSM-5 molecular sieve, then filter, dry, and calcine to obtain the modified ZSM-5 molecular sieve.
[0039] 3) Modified silicon material, modified ZSM-5 molecular sieve, Y-type molecular sieve, clay and binder and deionized water are mixed and pulped, then sprayed to form microspheres, and then calcined to obtain heavy oil catalytic cracking catalyst.
[0040] Therefore, the preparation method of the catalytic cracking catalyst provided by the present invention firstly modifies the silicon source with alkaline earth metals, boron and rare earths to obtain modified silicon material, forming metal active centers (first active centers); then, ZSM-5 molecular sieve is modified with metal nanoparticles to obtain modified ZSM-5 molecular sieve, forming mesoporous acid shape-selective catalytic active centers and alkane dehydrogenation active centers (third active centers); then, Y-type molecular sieve is mixed with modified silicon material, modified ZSM-5 molecular sieve, clay and binder, slurryed, spray-dried and calcined to obtain catalyst, using Y-type molecular sieve as macroporous acid catalytic active center (second active center), forming a catalytic cracking catalyst with three catalytic active centers.
[0041] From the perspective of pore structure, ZSM-5 molecular sieve belongs to mesoporous materials, Y-type molecular sieve belongs to macroporous materials, and silicon materials belong to ultra-large pore materials. This stepped pore design is conducive to the hierarchical and tandem cracking reaction of heavy oil macromolecules.
[0042] From the perspective of catalytic active centers, the alkaline earth metals in the first active center are the active centers for the alkane radical cracking reaction to generate olefins, boron acts as an accelerant for the alkaline earth metal reaction, and rare earth elements act as accelerants for heavy oil conversion. The first active center has two functions: first, it utilizes the large pores and weak acidity of silicon materials to achieve the pre-cracking of heavy oil macromolecules, and the addition of rare earth elements can enhance the pre-cracking reaction; second, the alkaline earth metal active center can undergo alkane radical cracking at high temperatures to generate ethylene, thus increasing ethylene production, and the addition of boron can enhance the role of the alkaline earth metals.
[0043] The Y-type molecular sieve with the second active center is a macroporous and moderately acidic catalytic material. Its function is to further acid-catalyze the pre-cracked macromolecules, i.e., to crack them by carbocation reaction to generate propylene, butene and larger hydrocarbon molecules.
[0044] The role of ZSM-5 zeolite in the third active center is to utilize its porous shape-selective catalytic properties and weak acidity to further catalyze the acid-selective catalysis of butene and larger hydrocarbon molecules, namely the carbocation cracking reaction to produce ethylene and propylene. Meanwhile, dehydrogenation active centers such as Fe, Co, Ni, Cu, and Ag can convert alkanes into alkenes, and the design of nanoparticles further enhances the effect of shape-selective catalysis to produce ethylene and propylene.
[0045] In this invention, the alkaline earth metal in the alkaline earth metal solution is at least one of Be, Mg, Ca, and Sr; the mass content of the alkaline earth metal in the alkaline earth metal solution, calculated as oxides, is 0.5% to 20%.
[0046] The boron-containing solution is any one of boric acid, trimethyl borate, or triethyl borate, and is soluble in water or hydrolyzable; preferably, the boron-containing solution is boric acid.
[0047] The silicon source in the silicon source solution is one or more of the following: tetraethyl orthosilicate, water glass, coarse-porous silica gel, silica sol, fumed silica, or activated clay.
[0048] The rare earth compounds are one or more of rare earth nitrates, rare earth chlorides, and rare earth carbonates.
[0049] In this invention, an alkaline earth metal solution is further prepared using an alkaline earth metal salt, wherein the alkaline earth metal salt is at least one selected from carbonates, nitrates, nitrites, sulfates, thiocyanates, phosphates, hydrogen phosphates, and chlorides.
[0050] The solvent for alkaline earth metal solutions is water or a mixture of water and alcohol containing at least one of methanol, ethanol, propanol, ethylene glycol, propylene glycol, or glycerol.
[0051] In this invention, the modified metal nanoparticle solution is further configured, specifically including:
[0052] A nanoparticle solution is prepared using a precursor salt of modified metal nanoparticles; a nanoparticle dispersant is added to the nanoparticle solution, followed by a liquid-phase chemical reducing agent to carry out a liquid-phase reduction reaction, thereby obtaining modified metal nanoparticles; the liquid-phase chemical reducing agent can be hydrazine hydrate.
[0053] The modified metal nanoparticles are at least one of Fe, Co, Ni, Cu, and Ag, and the average particle size of the modified metal nanoparticles is 0.5~200 nm.
[0054] The nanoparticle dispersant is at least one of ethylene glycol, propylene glycol, glycerin, polyacrylamide, and polyvinylpyrrolidone;
[0055] The nanoparticles are at least one of the following: metal, metal oxide, and metal sulfide of the modified metal.
[0056] The precursor salt of the modified metal nanoparticles is at least one of the nitrate, acetate, and chloride salts of the modified metal.
[0057] The nanoparticle solution contains 0.5% to 30% modified metal elements.
[0058] In this invention, the silicon-aluminum ratio of the ZSM-5 molecular sieve is further 10 to 300;
[0059] Y-type molecular sieves contain at least one of rare earth Y-type molecular sieves, rare earth hydrogen Y-type molecular sieves, ultrastable Y-type molecular sieves, and high-silica Y-type molecular sieves.
[0060] According to one technical solution of the present invention, the clay is at least one selected from soapstone, bentonite, kaolin, montmorillonite, diatomite, rettoitite, sepiolite, halloysite, attapulgite, hydrotalcite, and quasi-haloysite.
[0061] The binder is one or more of the following: alumina, silicon dioxide, titanium dioxide, magnesium oxide, zirconium oxide, thorium oxide, and beryllium oxide.
[0062] The present invention also provides a heavy oil catalytic cracking catalyst, which is prepared by the above-described method for preparing a heavy oil catalytic cracking catalyst. The heavy oil catalytic cracking catalyst comprises the following components by weight percentage: 20-50% ZSM-5 molecular sieve, 5-15% Y-type molecular sieve, 0.5-5% boron-containing compound, 0.5-5% modified metal nanoparticles, 0.5-5% rare earth oxides, and the remainder being clay and binder.
[0063] The present invention also provides a method for catalytic cracking of heavy oil, wherein heavy oil is contacted with a catalyst under catalytic cracking conditions and a catalytic cracking reaction is carried out under the action of high-temperature steam; the catalyst is the above-mentioned heavy oil catalytic cracking catalyst.
[0064] In this invention, the heavy oil is further selected from one or more of vacuum residue, atmospheric residue, vacuum gas oil, atmospheric gas oil, coking wax oil, deasphalted oil, and hydrotreated oil.
[0065] In this invention, the reaction conditions are further specified as follows: reaction temperature 510-700℃, reaction time 0.1-20s, agent-to-oil mass ratio 6-40:1, and water vapor to heavy oil mass ratio 0.1-1:1. Preferably, the reaction conditions are: reaction temperature 530-650℃, reaction time 1-5s, agent-to-oil mass ratio 15-30:1, and water vapor to heavy oil mass ratio 0.2-0.5:1.
[0066] The present invention will now be described in detail with reference to specific embodiments and comparative examples.
[0067] Example 1:
[0068] 1) Prepare a 50ml magnesium nitrate aqueous solution using magnesium nitrate hexahydrate and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add lanthanum nitrate and age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate and boric acid added, the main components of the modified silicon material, in terms of the ratio of corresponding oxides, are MgO:La2O3:B2O3:SiO2 = 6:8:6:80.
[0069] 2) Prepare a 50 ml ferric nitrate aqueous solution using ferric nitrate nonahydrate and deionized water. Add 5 g of polyacrylamide, and then add 5 times the equivalent molar amount of hydrazine hydrate at 75°C. Stir for 6 hours to form an iron nanoparticle solution with an average particle size of 30 nm. Then add 50 g of HZSM-5 (with a silicon-to-aluminum ratio of 50). Stir and mix at 30°C for 1 hour, then filter, dry at 120°C for 2 hours, and then calcine at 550°C for 4 hours to form a modified ZSM-5 molecular sieve.
[0070] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain microsphere catalysts, which were then calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst J-1. The mass content of different components in catalyst J-1 was as follows: Mg (equivalent to MgO) 3%, La (equivalent to La2O3) 4%, B (equivalent to B2O3) 3%, Fe (equivalent to Fe2O3) 1.1%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0071] Example 2:
[0072] 1) Prepare a 50ml calcium nitrate aqueous solution using calcium nitrate tetrahydrate and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add cerium nitrate and age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of calcium nitrate hexahydrate and boric acid added, the main components of the modified silicon material, in terms of the ratio of corresponding oxides, are CaO:Ce2O3:B2O3:SiO2 = 6:8:6:80.
[0073] 2) Prepare a 50 ml ferric nitrate aqueous solution using ferric nitrate nonahydrate and deionized water. Add 5 g of polyacrylamide, and then add 5 times the equivalent molar amount of hydrazine hydrate at 75°C. Stir for 6 hours to form an iron nanoparticle solution with an average particle size of 30 nm. Then add 50 g of HZSM-5 (with a silicon-to-aluminum ratio of 100). Stir and mix at 30°C for 1 hour, then filter, dry at 120°C for 2 hours, and then calcine at 550°C for 4 hours to form a modified ZSM-5 molecular sieve.
[0074] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain a microsphere catalyst, which was then calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst J-2. The mass content of different components in catalyst J-2 was as follows: Ca (equivalent to CaO) 3%, Ce (equivalent to Ce2O3) 4%, B (equivalent to B2O3) 3%, Fe (equivalent to Fe2O3) 2.3%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0075] Example 3:
[0076] 1) Prepare a 50ml magnesium nitrate aqueous solution using magnesium nitrate hexahydrate and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add lanthanum nitrate and age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate and boric acid added, the main components of the modified silicon material, in terms of the ratio of corresponding oxides, are MgO:La2O3:B2O3:SiO2 = 6:8:6:80.
[0077] 2) Prepare a 50 ml cobalt nitrate aqueous solution using cobalt nitrate nonahydrate and deionized water. Add 5 g of polyacrylamide, and then add 5 times the equivalent molar amount of hydrazine hydrate at 75°C. Stir for 6 hours to form a cobalt nanoparticle solution with an average particle size of 60 nm. Then add 50 g of HZSM-5 (with a silicon-to-aluminum ratio of 50). Stir and mix at 30°C for 1 hour, then filter, dry at 120°C for 2 hours, and then calcine at 550°C for 4 hours to form a modified ZSM-5 molecular sieve.
[0078] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain a microsphere catalyst, which was then calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst J-3. The mass content of different components in catalyst J-3 was as follows: Mg (equivalent to MgO) 3%, La (equivalent to La2O3) 4%, B (equivalent to B2O3) 3%, Co (equivalent to Co2O3) 2.5%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0079] Example 4:
[0080] 1) Prepare a 50ml magnesium nitrate aqueous solution using magnesium nitrate hexahydrate and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add lanthanum nitrate and age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate and boric acid added, the ratio of the main components formed, based on the corresponding oxides, is MgO:La2O3:B2O3:SiO2 = 6:8:6:80.
[0081] 2) Prepare 50 ml of an aqueous solution of ferric nitrate and cobalt nitrate using ferric nitrate nonahydrate, cobalt nitrate nonahydrate, and deionized water. Add 5 g of polyacrylamide, and then add 5 times the equivalent molar amount of hydrazine hydrate at 75°C. Stir for 6 hours to form an iron and cobalt nanoparticle solution with an average particle size of 70 nm. Then add 50 g of HZSM-5 (with a silicon-to-aluminum ratio of 50). Stir and mix at 30°C for 1 hour, then filter, dry at 120°C for 2 hours, and then calcine at 550°C for 4 hours to form a modified ZSM-5 molecular sieve.
[0082] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain a microsphere catalyst. The microsphere catalyst was calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst J-4. The mass content of different components in catalyst J-4 was as follows: Mg (equivalent to MgO) 3%, La (equivalent to La2O3) 4%, B (equivalent to B2O3) 3%, Fe (equivalent to Fe2O3) 1.0%, Co (equivalent to Co2O3) 1.2%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0083] Example 5:
[0084] 1) Prepare a 50ml aqueous solution using magnesium nitrate hexahydrate, calcium nitrate tetrahydrate, and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add lanthanum nitrate rare earth and age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate, calcium nitrate tetrahydrate, and boric acid added, the ratio of the main components, calculated as corresponding oxides, is MgO:CaO:La2O3:B2O3:SiO2 = 4:4:8:6:78.
[0085] 2) Prepare 50 ml of an aqueous solution of ferric nitrate and cobalt nitrate using ferric nitrate nonahydrate, cobalt nitrate nonahydrate, and deionized water. Add 5 g of polyacrylamide, and then add 5 times the equivalent molar amount of hydrazine hydrate at 75°C. Stir for 6 hours to form a cobalt nanoparticle solution with an average particle size of ~70 nm. Then add 50 g of HZSM-5 (with a silicon-to-aluminum ratio of 50). Stir and mix at 30°C for 1 hour, then filter, dry at 120°C for 2 hours, and then calcine at 550°C for 4 hours to form a modified ZSM-5 molecular sieve.
[0086] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain a microsphere catalyst, which was then calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst J-5. The mass content of different components in catalyst J-5 was as follows: Mg (equivalent to MgO) 2%, Ca (equivalent to CaO) 2%, La (equivalent to La2O3) 4%, B (equivalent to B2O3) 3%, Fe (equivalent to Fe2O3) 1.0%, Co (equivalent to Co2O3) 1.2%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0087] Example 6:
[0088] 1) Prepare a 50ml magnesium nitrate aqueous solution using magnesium nitrate hexahydrate and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add lanthanum nitrate and then age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate and boric acid added, the ratio of the main components formed, based on the corresponding oxides, is MgO:La2O3:B2O3:SiO2 = 6:8:6:80.
[0089] 2) Prepare a 50 ml ferric nitrate aqueous solution using ferric nitrate nonahydrate and deionized water. Add 5 g of polyacrylamide, and then add 5 times the equivalent molar amount of hydrazine hydrate at 75°C. Stir for 6 hours to form an iron nanoparticle solution with an average particle size of ~30 nm. Then add 50 g of HZSM-5 (with a silicon-to-aluminum ratio of 50). Stir and mix at 30°C for 1 hour, then filter, dry at 120°C for 2 hours, and then calcine at 550°C for 4 hours to form a modified ZSM-5 molecular sieve.
[0090] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) are mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry is spray-dried to obtain a microsphere catalyst, which is then calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst J-1. The mass content of different components in the catalyst is as follows: Mg (equivalent to MgO) 3%, La (equivalent to La2O3) 4%, B (equivalent to B2O3) 3%, Fe (equivalent to Fe2O3) 1.1%, HZSM-5 molecular sieve 30%, ultrastable Y-type molecular sieve 10%, and the remainder being binders and matrix such as SiO2 and alumina.
[0091] Comparative Example 1:
[0092] 1) Prepare a 50ml magnesium nitrate aqueous solution using magnesium nitrate hexahydrate and deionized water. Slowly add this solution to 500ml of silica gel solution with a 30% SiO2 content. Mix for 1 hour, then add lanthanum nitrate. Aging at 45℃ for 2 hours yields the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate added, the main components of the modified silicon material, expressed as corresponding oxides, are in the ratio of MgO:La2O3:SiO2 = 6:8:86.
[0093] 2) Take 50g of HZSM-5 (with a silicon-to-aluminum ratio of 50) and calcine it at 550℃ for 4h.
[0094] 3) The modified silicon material prepared in 1) and the HZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain a microsphere catalyst, which was then calcined at 520℃ for 3 hours to obtain catalytic cracking catalyst D-1. The mass content of different components in catalyst D-1 was as follows: Mg (equivalent to MgO) 3%, La (equivalent to La2O3) 4%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0095] Comparative Example 2:
[0096] 1) Prepare a 50ml magnesium nitrate aqueous solution using magnesium nitrate hexahydrate and deionized water. Slowly add boric acid and mix for 1 hour. Then, slowly add the solution to 500ml of silica gel solution with a 30% SiO2 content and mix for 1 hour. Next, add lanthanum nitrate and age at 45℃ for 2 hours to obtain the modified silicon material. By controlling the mass of magnesium nitrate hexahydrate and boric acid added, the main components of the modified silicon material, in terms of the ratio of corresponding oxides, are MgO:La2O3:B2O3:SiO2 = 6:8:6:80.
[0097] 2) Prepare a 50 ml aqueous solution of ferric nitrate using ferric nitrate nonahydrate and deionized water. Then add 50 g of HZSM-5 (silicon-to-aluminum ratio 50). Stir and mix at 30°C for 1 h. After filtration, dry at 120°C for 2 h, and then calcine at 550°C for 4 h to form modified ZSM-5 molecular sieve.
[0098] 3) The modified silicon material prepared in 1) and the modified ZSM-5 molecular sieve, ultrastable Y-type molecular sieve, pseudoboehmite, alumina sol, and kaolin prepared in 2) were mixed with hydrochloric acid at a weight concentration of 22% to obtain a slurry with a solid content of 35% by weight. The slurry was spray-dried to obtain a microsphere catalyst, which was then calcined at 500℃ for 2 hours to obtain catalytic cracking catalyst D-2. The mass content of different components in catalyst D-2 was as follows: Mg (equivalent to MgO) 3%, La (equivalent to La2O3) 4%, B (equivalent to B2O3) 3%, Fe (equivalent to Fe2O3) 1.1%, HZSM-5 molecular sieve 35%, ultrastable Y-type molecular sieve 8%, and the remainder being binders and matrix such as SiO2 and alumina.
[0099] The catalytic cracking catalysts J-1~J-6 prepared in Examples 1-6 and the catalytic cracking catalysts D-1 and D-2 prepared in Comparative Examples 1-2 were aged at 800°C and 100% steam for 4 hours. Their catalytic cracking reaction performance was evaluated in a small fixed fluidized bed device under the following conditions: reaction temperature 580°C, catalyst-to-oil mass ratio 10, and mass hourly space velocity 4 h⁻¹. -1 The water-to-oil mass ratio was 25%. The properties of the heavy oil used in the catalytic cracking reaction are shown in Table 1, and the reaction results are shown in Table 2.
[0100] As can be seen from the results listed in Table 2, the catalytic cracking catalyst provided by the present invention has higher heavy oil cracking capacity, higher ethylene and propylene yields, especially higher ethylene yield.
[0101] Table 1
[0102]
[0103] Table 2
[0104]
[0105] The above description is merely a partial embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above features with (but not limited to) technical features with similar functions disclosed in this application.
Claims
1. A method for preparing a heavy oil catalytic cracking catalyst, characterized in that, Includes the following steps: 1) Prepare an alkaline earth metal solution and a boron-containing solution, add the alkaline earth metal solution and the boron-containing solution to a silicon source solution, mix them evenly, then add a rare earth compound, and after aging, obtain a modified silicon material; 2) Prepare a modified metal nanoparticle solution, impregnate the modified metal nanoparticle solution with ZSM-5 molecular sieve, and then filter, dry and calcine to obtain modified ZSM-5 molecular sieve; 3) The modified silicon material, the modified ZSM-5 molecular sieve, the Y-type molecular sieve, clay and binder and deionized water are mixed and pulped, then sprayed to form microspheres, and then calcined to obtain a heavy oil catalytic cracking catalyst.
2. The method for preparing the heavy oil catalytic cracking catalyst according to claim 1, characterized in that, The alkaline earth metal in the alkaline earth metal solution is at least one of Be, Mg, Ca, and Sr; the mass content of the alkaline earth metal in the alkaline earth metal solution, calculated as oxides, is 0.5% to 20%. The boron-containing solution is any one of boric acid, trimethyl borate, and triethyl borate, and the boron-containing solution is soluble in water or hydrolyzable. The silicon source in the silicon source solution is one or more of the following: tetraethyl orthosilicate, water glass, coarse-porous silica gel, silica sol, fumed silica, or activated clay. The rare earth compound is one or more of rare earth nitrate, rare earth chloride, and rare earth carbonate.
3. The method for preparing the heavy oil catalytic cracking catalyst according to claim 2, characterized in that, The alkaline earth metal solution is prepared using an alkaline earth metal salt, wherein the alkaline earth metal salt is at least one selected from carbonates, nitrates, nitrites, sulfates, thiocyanates, phosphates, hydrogen phosphates, and chlorides. The solvent for the alkaline earth metal solution is water or a mixture of water and alcohol containing at least one of methanol, ethanol, propanol, ethylene glycol, propylene glycol, or glycerol.
4. The method for preparing the heavy oil catalytic cracking catalyst according to claim 1, characterized in that, The modified metal nanoparticle solution specifically includes: A nanoparticle solution was prepared using a precursor salt of modified metal nanoparticles; a nanoparticle dispersant was added to the nanoparticle solution, followed by a liquid-phase chemical reducing agent to carry out a liquid-phase reduction reaction, thereby obtaining modified metal nanoparticles. The modified metal nanoparticles are at least one of Fe, Co, Ni, Cu, and Ag, and the average particle size of the modified metal nanoparticles is 0.5~200 nm. The nanoparticle dispersant is at least one of ethylene glycol, propylene glycol, glycerin, polyacrylamide, and polyvinylpyrrolidone. The nanoparticles are at least one of the following: modified metal, metal oxide, and metal sulfide. The precursor salt of the modified metal nanoparticles is at least one of the nitrate, acetate, and chloride salts of the modified metal; The nanoparticle solution contains 0.5-30% modified metal elements.
5. The method for preparing the heavy oil catalytic cracking catalyst according to claim 1, characterized in that, The silicon-aluminum ratio of the ZSM-5 molecular sieve is 10~300; The Y-type molecular sieve is at least one of rare earth Y-type molecular sieve, rare earth hydrogen Y-type molecular sieve, ultrastable Y-type molecular sieve and high silica Y-type molecular sieve.
6. The method for preparing the heavy oil catalytic cracking catalyst according to claim 1, characterized in that, The clay is at least one of soapstone, bentonite, kaolin, montmorillonite, diatomite, rettoite, sepiolite, halloysite, attapulgite, hydrotalcite, and quasi-haloysite. The binder is one or more of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, zirconium oxide, thorium oxide, and beryllium oxide.
7. A heavy oil catalytic cracking catalyst, characterized in that, The heavy oil catalytic cracking catalyst is prepared by the method described in any one of claims 1 to 6, wherein the heavy oil catalytic cracking catalyst comprises the following components in weight percentage: 20-50% ZSM-5 molecular sieve, 5-15% Y-type molecular sieve, 0.5-5% boron-containing compound, 0.5-5% modified metal nanoparticles, 0.5-5% rare earth oxides, and the remainder being clay and binder.
8. A method for catalytic cracking of heavy oil, characterized in that, Under catalytic cracking conditions, heavy oil is contacted with a catalyst and subjected to catalytic cracking reaction under the action of high-temperature steam; the catalyst is the heavy oil catalytic cracking catalyst as described in claim 7.
9. The heavy oil catalytic cracking method according to claim 8, characterized in that, The heavy oil is one or more of the following: vacuum residue, atmospheric residue, vacuum gas oil, atmospheric gas oil, coking wax oil, deasphalted oil, and hydrotreated oil.
10. The heavy oil catalytic cracking method according to claim 8, characterized in that, The reaction conditions for the catalytic cracking reaction are as follows: reaction temperature of 510~700℃, reaction time of 0.1~20s, catalyst-to-oil mass ratio of 6-40:1, and steam-to-heavy oil mass ratio of 0.1~1:1.
Citation Information
Patent Citations
Heavy oil catalytic cracking catalyst
CN101310858A
A catalyst for heavy oil catalytic cracking to produce gasoline and low-carbon olefins, its preparation method and application
CN115532305B